Enhanced formula-based method to estimate burnup, initial enrichment, and cooling time using limited gamma-ray source data of reference PWR spent nuclear fuel assemblies - Sang Hyeok Lee; Jae Hak Cheong (Nuclear Engineering and Technology)
This study proposes a framework to develop a model for estimating burnup (BU), initial enrichment (IE), and cooling time (CT) of spent nuclear fuel (SNF) overcoming the limitations of existing models in determining IE. Database (DB) of gamma-ray sources for PWR SNF was generated using ORIGAMI. Target gamma radionuclides were selected based on the ease and credibility of measurement. The concept of Product of Powers of Radioactivity (PPR) was suggested, and PPRs for modeling were selected through evaluation of all possible PPRs. Functions established for PPRs were applied to estimate BU, IE, and CT (BIC) of PWR SNF assemblies. Optimized PPR combinations for estimating BU, IE, and CT respectively, as well as three variables simultaneously with the highest accuracy, were suggested. The estimation model proposed in this study enhanced IE estimations, maintaining the reliability of BU and CT estimations. The above framework enables construction of intuitive BIC estimation models using only a small amount of data. This can help hasten the development of estimation models for SNF from various reactor types. Consequently, it is expected to contribute to the safety and safeguards of SNF management by improving the verification that SNF meets acceptance criteria and conforms to the declared information.